The heart microbiome of insectivorous bats from Central and South Eastern Europe - Corduneanu, Alexandra; Mihalca, Andrei Daniel; Sandor, Attila D.; Hornok, Sándor; Malmberg, Maja; Pin Viso, Natalia Daniela; Bongcam-Rudloff, Erik (Elsevier, 2021)
Host associated microbiome not only may affect the individual health-status or provide insights into the species- or group specific bacterial communities but may act as early warning signs in the assessment of zoonotic reservoirs, offering clues to predict, prevent and control possible episodes of emerging zoonoses. Bats may be carriers and reservoirs of multiple pathogens such as viruses, bacteria and parasites, showing in the same time robust immunity against many of them. The microbiota plays a fundamental role on the induction, training and function of the host immune system and the immune system has largely evolved in order to maintain the symbiotic relationship of the host with these diverse microbes. Thus, expanding our knowledge on bat-associated microbiome it can be usefully in understanding bats’ outstanding immune capacities. The aim of this study was to investigate the presence of different bacterial communities in heart tissue of insectivorous bats, Nyctalus noctula, Pipistrellus pipistrellus and Rhinoplophus hipposideros, from Central and Eastern Europe using high-throughput sequencing of variable regions of the 16S rRNA. In addition, species-specific PCRs were used to validate the presence of the vector-borne pathogens Bartonella spp. and Rickettsia spp. In this study we identified a wide variety of bacterial groups, with the most abundant phyla being Proteobacteria and Firmicutes. The results showed that at individual level, the year or location had no effect on the diversity and composition of the microbiome, however host species determined both structure and abundance of the bacterial community. We report the presence of vector-borne bacteria Bartonella spp. in samples of N. noctula and indications of Rickettsia spp. in R. hipposideros. Our results provide a first insight into the bacterial community found in heart tissue of bats from Central and South Eastern Europe.